Trends and patterns in communication research on Asia: A review of publications in top SSCI journals, 1995-2014 - Liu, Xun "Sunny"; Wei, Ran (MedieKultur: Journal of media and communication research, 2017)
Communication research in Asia has enjoyed rapid growth in the 20th century amid Asia’s economic boom, rapid growth in communication technologies and expanded university faculty. To explore the extent to which the rise of Asian communication research continued in the 21st century, a total of 558 publications on Asian communication research in 14 top-ranked SSCI communication journals from 1995 to 2014 were analyzed. Results indicate that the rise of Asian communication research is afoot in the 21st century. However, the results of also suggest patterns of unevenness of the published scholarship in terms of publishing year, journals, region, research topics and methodology: Asian communication research was dominated by East Asia, which was dominated by China, South Korea and Japan; in terms of research areas by topic, Asian communication scholarship focused on a few areas, including media effects, political communication, communication technology, and health communication; in terms of research methodologies, the quantitative approach was found to be dominant in the publications, which accounts for more than twice that of qualitative research.